U.S. federal fire and forest policy: emphasizing resilience in dry forests. Issue 11 (11th November 2016) - Stephens, Scott L.; Collins, Brandon M.; Biber, Eric; Fulé, Peter Z.
Abstract: Current U.S. forest fire policy emphasizes short‐term outcomes versus long‐term goals. This perspective drives managers to focus on the protection of high‐valued resources, whether ecosystem‐based or developed infrastructure, at the expense of forest resilience. Given these current and future challenges posed by wildland fire and because the U.S. Forest Service spent >50% of its budget on fire suppression in 2015, a review and reexamination of existing policy is warranted. One of the most difficult challenges to revising forest fire policy is that agency organizations and decision making processes are not structured in ways to ensure that fire management is thoroughly considered in management decisions. Current resource‐specific policies are so focused on individual concerns that they may be missing the fact that there are "endangered landscapes" that are threatened by changing climate and fire. We propose that forest restoration should be at least equal to other land management priorities because large‐scale restoration is necessary for the sake of forest ecosystem integrity now and into the future. Another proposal is to switch the "default" rule in federal planning documents that currently have to "justify" managed wildland fire; instead, U.S. federal agencies should be required to disclose the long‐term ecological impacts of continued fire suppression. Proposed legislation that identifies the most expensive 2% of wildfires annually to be funded from emergency funding instead of by the federal land management agencies. If increases in forest restoration fail to accompany the change in how large wildfires are funded, then U.S. fire suppression costs will remain high while resilience will continue to decline. Expansion of the wildland–urban interface will continue to drive suppression costs higher; new federal partnerships with States and local governments are needed to address this problem. Given the legacy of fire suppression and a future of climate change, management for other values in forests will be, in the long run, futile without also managing for long‐term forest resilience.